Analyzing the Trends of Precipitation and Drought in Some Semi-Arid toHumid Regions of Iran - M. Nouri (علوم آب و خاک, 2018)
In this study, the trends of changes of the standardized precipitation index in a 12-month timescale (SPI-12) and seasonal and annual precipitation were investigated in 21 humid and semi-arid stations of Iran during the 1976-2014 time period. After removing the serial correlation of some series, the trend of precipitation and SPI-12 was detected using the Mann-Kendall nonparametric trend test. The results revealed that the trends of annual precipitation had been declining in all stations over the past 39 years.  The seasonal precipitation trend in winter, spring, autumn and summer was downward in approximately 90, 95, 47 and 37% of the studied stations, respectively. In addition, the descending trend of wintertime precipitation was significant in Sanandaj, Khoy, Urmia, Hamedan, Mashhad, Torbat-e-heydarieh, Nozheh and Qazvin. Also, the temporal trend of SPI-12 was decreasing in all surveyed stations except Shahrekord. Furthermore, SPI-12 showed a significant downward trend only in Sanandaj and Fasa. Moreover, the most severe meteorological drought occurred in the period 1999-2000, in Ramsar, Urmia and Hamedan, and in the period 2008-2009, in Tabriz, Sanandaj, Shiraz, Fasa, Qazvin, Mashhad, Torbat-e-heydarieh, Shahrekord, Gorgan and Kermanshah stations. Overall, the results of this study indicated that the trend of precipitation in most studied sites, particularly in semi-arid parts of the northeast and southwest of Iran, has changed due to the severe and long metrological drought that has occurred in the recent decade (2005-2015).